Hubungan Harga diri (Self Esteem) dengan Kenakalan Remaja Siswa Sekolah Menengah Pertama (SMP) - Suryandari, Savitri; Desiningrum, Noviana (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to determine the relationship between self-esteem and juvenile delinquency in Al Wachid Junior High School students in Surabaya. The subjects of this study are all students of Al Wachid Junior High School Surabaya totaling 150 people. Sampling was carried out by random sampling, using the Likert scale to collect research data, namely the self-esteem scale and the juvenile delinquency scale. The results of the study were analyzed using a regression technique with 6 special choices, and the results were F = 0.717, db = 2, p = 0.0506 (p > 0.05), which showed that there was no significant relationship between self-esteem and juvenile delinquency. Further findings showed that partially, self-esteem had no significant correlation with juvenile delinquency, with rx2y = -0.062, p = 0.053 (p > 0.05). Therefore, further research is suggested to explore other factors that may have a greater influence on juvenile delinquency, such as family environment, peer group, and socioeconomic conditions.